Influence of neuromuscular fatigue on co-contraction between vastus medialis and vastus lateralis during isometric contractions - da Silva, Cristiano Rocha [UNESP]; de Silva, Danilo Oliveira [UNESP]; Aragão, Fernando Amâncio [UNESP]; Ferrari, Deisi [UNESP]; Alves, Neri [UNESP]; de Azevedo, FáBio Mícolis [UNESP] (My University, 2014)
The aim of this study was to evaluate the effect of neuromuscular fatigue on vastus medialis and vastus lateralis co-contraction. Fifteen healthy young subjects performed an isometric leg extension test in two different condition phases: i) maximum test for determining the maximum voluntary isometric contraction, and ii) fatigue test for exercises executed at 50% of the maximum voluntary contraction in three distinct periods with seven-day intervals between the tests. To quantify the co-contraction between the vastus medialis and vastus lateralis muscles, the signals overlapped and the intersection area was calculated. The data reliability was verified with the intraclass correlation coefficient (ICC) and standard error measurement (SEM). Values of median frequency and root mean square for both muscles showed a significant difference between the beginning and the end of the test, which indicates occurrence of the neuromuscular fatigue. The median frequency and root mean square ICC values ranged from moderate (ICC.66) to high (ICC.74) reliability with low SEM both for vastus medialis and vastus lateralis. The co-contraction values in the beginning of the test varied from 0.76 to 0.77, with a moderate reliability (ICC.63) and with low SEM. In the neuromuscular fatigue condition, ICC values of co-contraction varied from.75 to.76, with low reliability (.14) and with low SEM. Therefore, there were no significant differences between the co-contraction behavior at the beginning and the end of the fatigue tests. Based on these results, it is understood that the neuromuscular fatigue does not alter muscle co-contraction between vastus medialis and vastus lateralis in maximum voluntary contraction tests.
Keywords: Electromyography; Muscles; Reproducibility of results